Underutilized crops in the production systems, livelihoods and diets of farmers in Chiquimula, Guatemala: Baseline results from the programme “Linking agrobiodiversity value chains, climate adaptation and nutrition: Empowering the poor to manage risk” - Bioversity International; Universidad del Valle (2017)
This household survey provided an overview of the production and livelihood systems of 88 households in three communities in Chiquimula district of Guatemala. The communities surveyed were among those targeted by the programme “Linking agrobiodiversity value chains, climate adaptation and nutrition: Empowering the poor to manage risk” funded by IFAD and the European Commission from 2015 to 2018. The programme aimed to strengthen the capacities of farmers to manage risks associated with climate change, poor nutrition status, and economic disempowerment through agrobiodiversity-based solutions. Enhancing productivity and promoting use of nutritious and climate-hardy underutilized species was the core of the initiative, which focused on chaya (Cnidoscolus aconitifolius) and tepary bean (Phaseolus acutifolius) in Guatemala. The survey documented the level of cultivation, commercialization, and consumption of chaya and revealed some clues to how chaya and tepary bean could contribute to improving food security, nutrition, and incomes in the surveyed communities. Chaya was cultivated by about a quarter of households in the surveyed villages. It was predominantly used for household consumption. Aside from limited trading within the community, chaya was not being marketed. Low consumption of vegetables revealed in the 24-hour diet recall shows that chaya could contribute to more balanced diets, especially in the lean season when there is less frequent consumption of vegetables. Tepary bean was not cultivated or consumed in the surveyed communities but common bean was grown by the majority of households and was an income source for several households. No other pulses were grown in the community and there was high reliance on common bean for dietary protein. The greater drought tolerance of tepary bean means it could help ensure a more stable and resilient pulse production for the communities and, with attention to value chain development, could also provide an income source.